No association of leg strength asymmetry with walking ability, fatigability, and fatigue in multiple sclerosis. Issue 3 (September 2018) - Proessl, Felix; Ketelhut, Nathaniel B.; Rudroff, Thorsten
Abstract : This cross-sectional study aims to determine whether leg strength asymmetries are associated with walking ability, objective measures of fatigability, or subjective perceptions of fatigue. Maximal knee extensor strength was assessed in 19 patients with multiple sclerosis (PwMS), and a symmetry index was calculated. Walking ability was determined through the total distance covered during a 6-min walk test (6MWT) and fatigability by calculating the change in distance covered between minutes 6 and 1. Perceptions of fatigue were assessed using the Fatigue Severity Scale and by obtaining ratings of perceived exertion during the first and final minute of the 6MWT. PwMS covered less distance ( P =0.01) and perceived greater exertion ( P <0.01) during minute 6 compared with minute 1. Knee extensor strength was asymmetric ( P <0.01). The magnitude of asymmetry did not correlate with walking ability, fatigability, or measures of fatigue. Knee extensor strength asymmetry may not play an important role in prolonged walking performance in PwMS.